A hydrogen gas sensor based on TiO₂ nanoparticles on alumina substrate - Mohd Chachuli, Siti Amaniah; Hamidon, Mohd Nizar; Mamat @ Mat Nazir, Md Shuhazlly; Ertugrul, Mehmet; Abdullah, Nor Hapishah (MDPI Multidisciplinary Digital Publishing Institute, 2018)
High demand of semiconductor gas sensor works at low operating temperature to as low as 100 ◦C has led to the fabrication of gas sensor based on TiO₂ nanoparticles. A sensing film of gas sensor was prepared by mixing the sensing material, TiO₂ (P25) and glass powder, and B₂O₃ with organic binder. The sensing film was annealed at temperature of 500 ◦C in 30 min. The morphological and structural properties of the sensing film were characterized by field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). The gas sensor was exposed to hydrogen with concentration of 100–1000 ppm and was tested at different operating temperatures which are 100 ◦C, 200 ◦C, and 300 ◦C to find the optimum operating temperature for producing the highest sensitivity. The gas sensor exhibited p-type conductivity based on decreased current when exposed to hydrogen. The gas sensor showed capability in sensing low concentration of hydrogen to as low as 100 ppm at 100 ◦C.